Model of Social Support for Adolescent Mental Health with Disabilities.. (Medico Legal Update, 2020)
For adolescents, disability is more than a physical limitation. Discrimination, social stigma, and pressure from the environment can induce a social limitation that excludes them from social. The lack of support causes them to suffer from physical limitations that will affect their mental health, and worse will create not only physically disable but also impact their life. This study aims to find an appropriate social support model for maintaining the mental health of adolescents with disabilities from examining the factors of adolescents’ characteristics, family, peers, health workers, and community leaders. This research method used cross sectional study, a total of 100 adolescents with disabilities from Cerebral Palsy Center Jakarta and Surakarta special schools were involved in this observation. This research consisted of collecting data, conducting FGD with teachers, health workers, family, and processing data with Smart-PLS. The results was that the adolescent mental health with disabilities were formed by individual characteristics (such as age, gender, education), the role of family, friends and teachers. Support from family, friends, teachers, community leaders in their roles are needed in stabilizing emotions and maintaining mental health of adolescents with disabilities.